Stock Market Return, Market Capitalization and Financial Stability in the Middle East and North Africa Region: The Moderating Role of Renewable Energy - Mbarek, Hassene Ben (International Journal of Energy Economics and Policy, 2026)
This study investigates the relationship between stock market return, stock market capitalization, and financial stability in the Middle East and North Africa (MENA) region, with particular emphasis on the moderating role of renewable energy development. Using an unbalanced panel of 16 MENA countries over the period 2000–2021, the analysis employs the System Generalized Method of Moments (SGMM) to address potential endogeneity, unobserved heterogeneity, and dynamic effects. The results indicate several important results. First, stock market return has a positive and significant effect on financial stability, suggesting that higher equity performance contributes to increased financial stability. In contrast, stock market capitalization shows a positive but statistically insignificant effect. Furthermore, findings also indicate that a higher share of renewable energy significantly enhances financial resilience. Nevertheless, the interactions term between stock market return, stock market capitalization and renewable energy do not exert any significant effect on financial stability. These findings imply that financial stability in the MENA region is primarily driven by market performance and the integration of renewable energy, while the sheer size of the stock market plays a limited role. Policies promoting renewable energy and stronger equity performance could therefore jointly enhance banking sector resilience.